Contributions of trade in shea-butter (vitellaria paradoxa) products to the rural economy in Saki, Oyo State, Nigeria (2013)
Involvement of rural people in forest-based activities can support private sector entrepreneurial development especially in communities that are endowed with forest resources. Shea butter (Vitelleria paradoxa) is a Non Timber Forest Resource (NTFR) of wide occurrence in Saki town, southwestern Nigeria. A survey was conducted to assess the involvement of residents’ in shea butter business/enterprise and by extension, its contribution to the study area economy. Four (4) categories of practitioners in shea butter business were identified viz: retailers (20.2%), processors (20.3%), gatherers (20.4%) and middlemen (39.3%). Women involvement in the business was over 70% in each of the categories. Again, respondents of various age classes are engaged in the business and mostly had little or no formal education (over 50.0%). This is an indication that shea butter business in the area was based more on homegrown training. This has serious implication for product standards and by extension wider market acceptability. Profits derived from the business was in the range of N91, 333 and N409, 747 per annum, which acceptably can contribute meaningfully to household and national poverty reduction. Training of local populations especially processors in modern methods of resources improvement (raw materials), product value addition methods and marketing strategies will complement local and national economic development efforts particularly at the grassroots’ level.